Extraction and Physicochemical Characterization of Mucilage from Opuntia cochenillifera (L.) Miller - Mariel Monrroy; Erick García; Katherine Ríos; José Renán García (Journal of Chemistry)
The aim of this study was to extract mucilage from O. cochenillifera (L.) cacti and determine its functional and physicochemical properties. The best mucilage yield (31%) was obtained by nonthermal extraction with hydration. The mucilage has appreciable carbohydrate and protein contents. The phytochemical analysis shown the presence of alkaloids and terpenes/steroids. The Fourier transformed infrared (FT-IR) spectrum of the mucilage exhibits typical bands for carbohydrates as O–H, C–H, and –COO−. The mucilage demonstrated water- and oil-holding capacities of 2.78 g water/g dry mucilage and 1.80 g oil/g dry mucilage, respectively, these properties can have a positive effect on the texture of the products when used as a stabilizer. The mildly acidic pH (4.8–5) contributes to its emulsifying capacity. The presence of electrolytes in the mucilage can be of great value in flocculation processes. The mucilage forms low viscosity solutions in the same manner as gum Arabic. Finally, its potential for use as a textile dye remover was evaluated, achieving a 70% removal rate from aqueous solutions. The prepared mucilage exhibits properties that recommend it as a natural material that can be used as an additive in the chemical, food, pharmaceuticals and cosmetics industries, as well as in decontamination processes.